KALAM KLASIK DAN KALAM KONTEMPORER (STUDI KONSTRUKSI METODOLOGI) - Ahmad, Muhammad Kursani (Jurnal Ilmu Ushuluddin, 2014)
The methodology of kalam in Islamic thought was born and developed by islamic experts as an attempt to translatethe values of universality al-Quran and al-Hadith. Here, they expressed his views of kalam, then maintained itthrough rational-logical argument, which is adapted to the circumstances age. The methodology of classical kalamthinking was the answers to the problems of kalam in passed time, which can be identified as from political strife, andphilosophical mindset, especially for flow of kalam which have relation with the Greek philosophical thought, and itâstheocentric oriented. While the methodology of kalam contemporary thought have in touch with contemporary Westernphilosophical thought today, its presence is not merely an attempt apoligetik defending God, but that is more anthropocentricexpected to help, overcome and solve the problems of society today.